1996
DOI: 10.1007/bf01780642
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infection in cystic fibrosis patients: Implications for the use of adenoviral vectors for gene transfer

Abstract: Clinical trials using replication-deficient adenovirus as vectors for gene transfer into the airways of cystic fibrosis (CF) patients are in progress. However, little is known about the prevalence of wild-type adenovirus infections in patients with cystic fibrosis and their effect on lung function. To answer these questions, serum IgG and IgM antibody titers against adenovirus type 5 were prospectively measured by an indirect immunofluorescence assay in 199 CF outpatients and in a control group of 45 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
2
19
1
1
Order By: Relevance
“…First, with regard to the safety of adenovectors for clinical use, no evidence for the appearance of replication-competent adenovirus was noted in 164 biologic specimens processed after injection of AdCAIL-2 using highly sensitive PCR assays or by culture on A549 cells. Indeed in contrast to reports from patients with cystic fibrosis, 26,27 no evidence for the presence of RCA infection or Ad5 E1 sequences was noted by PCR of DNA from 250 samples of blood, saliva or tumor taken either before or after injection of AdCAIL-2. We can conclude that endogenous Ad5 E1 DNA sequences are uncommon in the tissues studied in this trial population and that the potential for in vivo endogenous complementation of E1-defective adenoviruses is therefore very low.…”
Section: Discussioncontrasting
confidence: 74%
“…First, with regard to the safety of adenovectors for clinical use, no evidence for the appearance of replication-competent adenovirus was noted in 164 biologic specimens processed after injection of AdCAIL-2 using highly sensitive PCR assays or by culture on A549 cells. Indeed in contrast to reports from patients with cystic fibrosis, 26,27 no evidence for the presence of RCA infection or Ad5 E1 sequences was noted by PCR of DNA from 250 samples of blood, saliva or tumor taken either before or after injection of AdCAIL-2. We can conclude that endogenous Ad5 E1 DNA sequences are uncommon in the tissues studied in this trial population and that the potential for in vivo endogenous complementation of E1-defective adenoviruses is therefore very low.…”
Section: Discussioncontrasting
confidence: 74%
“…Rosenecker et al 22 in a noteworthy report demonstrated that IgG antibodies against adenovirus were present in 192 of 199 cystic fibrosis patients (96.5%), and were significantly higher in cystic fibrosis patients older than 7 years than in younger patients and in age matched controls. Surveillance carried out in Japan by the SRL laboratory (Hachioji, Tokyo, Japan) between 1993 and 1995 revealed that approximately 75% and 72% of Japanese possess neutralizing antibodies against adenovirus serotype-2 and -5, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The use of viral vectors for gene therapy has progressed to clinical trials [1][2][3][4][5][6][7][8] which, to date, have involved vector delivery through injection of a liquid suspension of viral particles. However, injection of virions yields inefficient localization of the vector at diseased target sites.…”
Section: Introductionmentioning
confidence: 99%